2020
DOI: 10.21873/invivo.12039
|View full text |Cite
|
Sign up to set email alerts
|

Oral Methioninase Inhibits Recurrence in a PDOX Mouse Model of Aggressive Triple-negative Breast Cancer

Abstract: Background/Aim: The aim of the study was to use a triple-negative breast cancer (TNBC) patient-derived orthotopic xenograft (PDOX) model to examine the efficacy of oral recombinant methioninase (o-rMETase) against this recalcitrant disease. Materials and Methods: The TNBC tumor from a patient was implanted in the right 4 th inguinal mammary fat pad of nude mice. Two weeks later, the mice underwent tumorectomy with grossly-negative surgical margins. Two days after tumorectomy the mice were divided in two groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…o-rMETase has already shown promise in the clinic (28) and will soon be tested on TNBC patients, especially with liver metastasis. o-rMETase has previously shown efficacy to inhibit post-surgical recurrence of TNBC in a PDOX nude-mouse model (30). This new PDOX model of TNBC liver metastasis has potential to identify curative therapeutics for this recalcitrant disease, especially using o-rMETase instead of injectable rMETase which can cause immunological reactions (31), unlike o-rMETase (28), and will therefore, be suitable clinically in the near future for TNBC.…”
Section: Discussionmentioning
confidence: 99%
“…o-rMETase has already shown promise in the clinic (28) and will soon be tested on TNBC patients, especially with liver metastasis. o-rMETase has previously shown efficacy to inhibit post-surgical recurrence of TNBC in a PDOX nude-mouse model (30). This new PDOX model of TNBC liver metastasis has potential to identify curative therapeutics for this recalcitrant disease, especially using o-rMETase instead of injectable rMETase which can cause immunological reactions (31), unlike o-rMETase (28), and will therefore, be suitable clinically in the near future for TNBC.…”
Section: Discussionmentioning
confidence: 99%
“…r-METase effectively degrades external methionine (63). The efficacy of orally-administrated r-METase (o-rMETase) was shown previously shown in many types of cancer in PDOX models (18,21,22,(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(51)(52)(53)(54)(55)(56)(57)(58). We have also reported the efficacy of rMETase on PDOX models of osteosarcoma including o-rMETase (8,10,18,21,22).…”
Section: Discussionmentioning
confidence: 78%
“…o-rMETase has also been shown to prevent obesity, diabetes and fatty liver in mouse models (47)(48)(49). o-rMETase has also shown apparent clinical efficacy in advanced prostate cancer (50), reflecting its efficacy in PDOX models of advanced cancers (51)(52)(53)(54)(55)(56)(57)(58).…”
Section: 100 Respectively) Only the Combination Of O-rmetase And Mtx Reduced The Cancer-cell Density In The Osteosarcoma Tumor Conclusiomentioning
confidence: 99%
“…For example, o-rMETase could overcome gemcitabine resistance in a PDOX model of pancreatic cancer (25). o-rMETase overcame chemotherapy-resistance in sarcoma (26)(27)(28) and triple-negative breast cancer (29,30). Early clinical studies have shown that o-rMETase decreases or stabilizes prostate specific antigen (PSA) levels in patients with advanced-prostate cancer with no adverse effects (31)(32)(33).…”
mentioning
confidence: 99%